SPINEL-SAPPHIRINE-QUARTZ BEARING COMPOSITE INCLUSION WITHIN GARNET FROM AN ULTRAHIGH-TEMPERATURE PELITIC GRANULITE: IMPLICATIONS FOR METAMORPHIC HISTORY AND P-T PATH - Tsunogae T.; Santosh M. (My University, 2006)
We report here a multiphase mineral inclusion composed of quartz, plagioclase, K-feldspar, sapphirine, spinel, orthopyroxene, and biotite, in porphyroblastic garnet within a pelitic granulite from Rajapalaiyam in the Madurai Granulite Block, southern India. In this unique textural association, hitherto unreported in previous studies, sapphirine shows four occurrences: (1) as anhedral mineral between spinel and quartz (Spr-1), (2) subhedral to euhedral needles mantled by quartz (Spr-2), (3) subhedral to anhedral mineral in orthopyroxene, and (4) isolated inclusion with quartz (Spr-4). Spr-1, Spr-2, and Spr-4 show direct grain contact with quartz, providing evidence for ultrahigh-temperature (UHT) metamorphism at temperatures exceeding 1000 °C. Associated orthopyroxene shows high Mg/(Fe + Mg) ratio (~ 0.75) and Al2O3 content (up to 9.6 wt.%), also suggesting T > 1050 °C and P > 10 kbar during peak metamorphism. Coarse spinel (Spl-1) with irregular grain morphology and adjacent quartz grains are separated by thin films of Spr-1 and K-feldspar, suggesting that Spl-1 and quartz were in equilibrium before the stability of Spr-1 + quartz. This texture implies that the P-T conditions of the rock shifted from the stability field of spinel + quartz to sapphirine + quartz. Petrogenetic grid considerations based on available data from the FMAS system favour exhumation along a counterclockwise P-T trajectory. The irregular shape of the inclusion and chemistry of the inclusion minerals are markedly different from the matrix phases suggesting the possibility that the inclusion minerals could have equilibrated from cordierite-bearing silicate-melt pockets during the garnet growth at extreme UHT conditions. © 2006 Elsevier B.V. All rights reserved.
Keywords: COUNTERCLOCKWISE P-T PATH; GRANULITE FACIES; MADURAI BLOCK; SOUTHERN INDIA; SPINEL + SAPPHIRINE + QUARTZ; ULTRAHIGH-TEMPERATURE METAMORPHISM